2015
DOI: 10.1007/s00586-015-3768-6
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle screw loosening: a clinically relevant complication?

Abstract: Reported loosening rates primarily depended on the protocol used for the clinical examination during follow-up and on the conventions used for the radiological assessment. Aiming to a better comparability of published data, we recommend the authors of clinical studies to describe which criteria were used to assess a loosened screw, as well as the protocol of the clinical follow-up examination. Low-dose CT should be used for the assessment of screw loosening whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
269
2
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(289 citation statements)
references
References 71 publications
4
269
2
14
Order By: Relevance
“…In our series (approximately 2/3 survival at 24 months), 12.5 % of treated lesions with available follow-up imaging (mean 8.7 months) demonstrated poor osseous consolidation or screw loosening; and at least 1 patient was symptomatic. Despite limited sample size and data quality, local unfavourable evolution at imaging follow-up may be relatively frequent similar to surgical series [28,32]. Our non-consolidated case can be explained by poor osseous substrate in a post-ablation cavity.…”
Section: Discussioncontrasting
confidence: 44%
“…In our series (approximately 2/3 survival at 24 months), 12.5 % of treated lesions with available follow-up imaging (mean 8.7 months) demonstrated poor osseous consolidation or screw loosening; and at least 1 patient was symptomatic. Despite limited sample size and data quality, local unfavourable evolution at imaging follow-up may be relatively frequent similar to surgical series [28,32]. Our non-consolidated case can be explained by poor osseous substrate in a post-ablation cavity.…”
Section: Discussioncontrasting
confidence: 44%
“…4,5 The complications and drawbacks of PMMA have also gradually been unveiled during clinical practice in the past few years. [1][2][3] Most drawbacks originate from the excessive mechanical strength or stiffness and nondegradability of PMMA, with its intrinsic material properties difficult to alter. This requires a new injectable material distinct from PMMA, but also be able to prevent pullout of screws from the vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of bone mass in osteoporotic patients greatly decreases the fixation strength of pedicle screws, causing loosening or pullout of screws, cutout of the vertebral body, failure of fixation, and a number of potential risks or complications. [1][2][3] Augmentation with bone cement has been demonstrated to be an effective way to increase the fixation strength of pedicle screws in osteoporotic patients. Previous studies have reported that the pullout strength of pedicle screws can be dramatically increased by augmentation with nondegradable or bioabsorbable bone cements such…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the difference for loosening between cranial and caudal screws should be discussed with care and have not been further reported. This may therefore be different in patients [6].…”
Section: Discussionmentioning
confidence: 98%
“…Pedicle screw systems are currently the most common technique for the stabilization of the spine, which requires a stable fixation in the bone [4,5]. But a poor bone mineral density in osteoporotic patients can result in a screw loosening [6][7][8][9]. Lamina hook systems have the advantage that they are connected directly to the lamina, which may have the advantage of a minimized injury risk for neural structures.…”
Section: Introductionmentioning
confidence: 99%